2018
DOI: 10.3389/fpsyt.2018.00532
|View full text |Cite
|
Sign up to set email alerts
|

Pre-treatment Resting-State Functional MR Imaging Predicts the Long-Term Clinical Outcome After Short-Term Paroxtine Treatment in Post-traumatic Stress Disorder

Abstract: Background: The chronic phase of post-traumatic stress disorder (PTSD) and the limited effectiveness of existing treatments creates the need for the development of potential biomarkers to predict response to antidepressant medication at an early stage. However, findings at present focus on acute therapeutic effect without following-up the long-term clinical outcome of PTSD. So far, studies predicting the long-term clinical outcome of short-term treatment based on both pre-treatment and post-treatment functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 56 publications
(69 reference statements)
1
17
0
Order By: Relevance
“…Further SVR results revealed that the high NH levels at baseline in the bilateral superior MPFC could predict symptomatic improvement of PANSS after 8 weeks of DPP treatment. Previous studies revealed that the orbital frontal cortex and dorsal MPFC were related to predicting the long-term clinical outcome in the post-traumatic stress disorder (47). The hemodynamic activities of the frontotemporal cortex may predict treatment response to selective serotonin reuptake inhibitor in MDD (48).…”
Section: Discussionmentioning
confidence: 99%
“…Further SVR results revealed that the high NH levels at baseline in the bilateral superior MPFC could predict symptomatic improvement of PANSS after 8 weeks of DPP treatment. Previous studies revealed that the orbital frontal cortex and dorsal MPFC were related to predicting the long-term clinical outcome in the post-traumatic stress disorder (47). The hemodynamic activities of the frontotemporal cortex may predict treatment response to selective serotonin reuptake inhibitor in MDD (48).…”
Section: Discussionmentioning
confidence: 99%
“…Resting‐state fMRI is a popular alternative, because it measures behaviourally‐relevant, synchronized brain network activity at rest, and the imaging protocols can be more easily harmonized across scanners 165 . Studies in this field have demonstrated similar accuracies for CBT 166 , trauma‐focused psychotherapy 167 , antidepressant treatment 168 , and antipsychotic therapy 169 , while also showing predictive accuracy for ECT 165,170 .…”
Section: The Use Of Data From Genetics Electrophysiology Neuroimaging and Cognitive Testingmentioning
confidence: 99%
“…However, only two studies to date have used machine learning analyses to predict future outcome at an individual level. One study aimed to predict clinical status two years after treatment with 12 weeks of paroxetine in a sample of 20 civilian PTSD patients 24 . This study used pre- and post-treatment rs-fMRI derived measures, namely amplitude of low-frequency fluctuations and whole-brain degree centrality maps, and the results showed that pre- but not post-treatment measures were able to predict remission status after two years with an accuracy of 72.5%.…”
Section: Introductionmentioning
confidence: 99%